The Influence of Workload and Work Discipline on the Job Satisfaction of Outsourced Employees at PT XYZ - Nabila Fitri Salsabila; Hesty Prima Rini (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose –  The increasingly competitive world of work requires organizations to have dynamic and sustainable human resources. The population and sample of this study consisted of all 50 outsourced employees in the production division of PT XYZ. The results revealed that workload has a negative and significant effect on employee job satisfaction, whereas work discipline has a positive and significant effect on job satisfaction. These findings highlight that maintaining a balance in workload and consistently applying discipline are crucial factors in maximizing employee job satisfaction. Design/methodology/approach – This study used a quantitative approach to examine the effects of workload and work discipline on the job satisfaction of 50 outsourced employees in the production division of PT XYZ. Total sampling was applied, and data were collected through questionnaires, interviews, and literature review. The data were analyzed using Partial Least Squares (PLS) to assess the validity, reliability, and significance of relationships between variables. This approach provides insights into the impact of workload and work discipline on employee job satisfaction and offers practical implications for human resource management. Originality - This study is original in examining the combined effects of workload and work discipline on the job satisfaction of outsourced employees at PT XYZ, providing practical insights for human resource management. Findings and Discussion – The findings of this study reveal that workload negatively affects the job satisfaction of outsourced employees at PT XYZ, particularly when excessive time demands lead to fatigue and stress. In contrast, work discipline positively influences job satisfaction, as higher compliance with rules and procedures enhances employees’ sense of responsibility, motivation, and engagement. The discussion emphasizes that balancing workload and promoting consistent work discipline are essential for creating a productive, orderly, and supportive work environment. These results provide practical implications for human resource management, highlighting the need for effective task distribution, realistic scheduling, and supervisory oversight to optimize employee satisfaction and performance. Conclusion –  In conclusion, workload negatively affects job satisfaction, while work discipline has a positive impact. Balancing workload and promoting consistent discipline are essential for enhancing employee satisfaction, motivation, and overall performance.